Challenging diagnostic of juvenile systemic sclerosis in limited sources: a case report - Ronaldi, Melissa; Wati, Ketut Dewi Kumara; Gunawijaya, Eka; Yantie, Ni Putu Veny Kartika; Anandasari, Pande Putu Yuli (Medical Faculty of Brawijaya University, Indonesia, 2024)
Background: Juvenile Systemic Sclerosis (JSSc) is a rare chronic-autoimmune rheumatic disease leading to potential delay in diagnosis, especially in limited sources due to lack of knowledge and facility. This case report aimed to present a rare case of JSSc in limited sources of medical facilities. Case presentation: A 15-year-old girl was earlier suspected of having congenital heart disease due to the presentation of bluish fingers without any detectable clinical heart disease manifestation, including normal electrocardiography as well as echocardiography. The patient experienced pain and difficulty executing wrist endorotation, representing limited joint movement action. Further physical examinations showed pale, cold fingers and toes, bluish color in the peripheral represented sclerodactyly and arthritis. Skin showed multiple erythema-hypopigmentation papuls, in accordance with gottorn papule, gottorn sign. The antinuclear antibody titer was 1:320. Chest CT-Scan result was a fibrotic line at the inferior lobe of the left lung with the left diaphragm tenting due to a chronic inflammatory process. Skin biopsy shows an acanthotic epidermis, dermafibrocollagenous tissue with extensive fibrosis, and sclerosis with vascular proliferation. These findings meet JSSc PRES, ACR, and EULAR standard classification criteria, including 1 major and 4 minors. The treatment regimen was started with methylprednisolone 2 mg/kg/day, then tapering off once clinical manifestation alleviated, methotrexate 10 mg/BSA, and folic acid 1 mg a day. Long-term monitoring plans are also scheduled. Conclusion: Recognizing early symptoms of JSSc would provide a better outcome.